Analysis of forage balances in the Djelfa region from 2001-2015. What is the place of pastoral and cultivated resources? - Meguellati A.; Kanoun M.; Saadaoui M.; Huguenin J.; Bekai F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The degradation of pastoral resources has been accelerated as a result of the severe droughts in the 1970s and 1980s. In addition to that, the new land practices had a major impact resulting in a territorial dynamic recomposition. They have led to a scarcity of the available forage for rangelands by reducing their surface area and their productivity. This study aims to analyze the ability of agropastoralists to adapt to this uncertain context of forage availability and to maintain the level of animals’ production. To do this, forage balances were computed during a period from 2001 to 2015 in the Djelfa region. The data studied came from the Department of Agricultural Statistics of the Ministry, the agricultural services of Djelfa and surveys of agropastors. Univariate descriptive statistical analysis showed a diversity of forage resources used to fulfil the nutritional requirements of animals. The share of pastoral supplies from home terroirs and pastures from transhumance contributes to 58% of animal needs. Thus,the pastoral resources remain decisive in the pastoralists’ strategy for animal feeding. Nevertheless, the contribution of grown fooder and purchased feed is growing. It accounted for nearly 38%, of which 58% and 42% are concentrated feed purchased (mainly grain) and fodder grown (mainly barley in green), respectively. However, coefficients of variation ranging from 20% to 77% imply that both access to pasture and the contribution of forage resources remain irregular, uncertain and monetarised.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)